The Role of Active Learning in Enhancing the Quality of the Educational Process An Analytical Study of Faculty Members at the College of Education in Zuwarah (Comprehensive Journal of Science, 2026)
This study aimed to identify the role of active learning in improving the educational process among faculty members at the Faculty of Education in Zwara. It focused on analyzing the current use of active learning strategies and their impact on student engagement and skill development. The study adopted the descriptive-analytical method and used a questionnaire as the main tool for data collection from a sample of 44 faculty members. The instrument included several dimensions, such as active learning strategies, factors influencing their implementation, use of technology, development of critical thinking, and the level of faculty satisfaction with active learning in enhancing the educational process.The results showed a high level of active learning implementation, with a strong emphasis on interactive methods such as group work and discussion. However, the findings also revealed a relative weakness in the use of educational technology. The study confirmed a strong relationship between active learning and the improvement of the educational process, in addition to its effective role in developing students’ critical thinking skills.In light of these findings, the study recommended enhancing the application of active learning, training faculty members, providing a supportive learning environment, and developing technological infrastructure to improve the quality of higher education.
Keywords: Active Learning, Educational Process, Faculty Members, Faculty of Education Zwara.